Phonological Trajectories in Down Syndrome: A Multidimensional Analysis - Vergara Ponce, Patricio; Heredia Tudela, Francisca; Parada Morollón, Jorge; Vega Rodríguez, Yuri; Diez Itza, Eliseo (Revista de Investigación en Logopedia, 2026)
Phonological development in individuals with Down syndrome (DS) follows a complex and extended trajectory, characterised by marked intra-individual variability that compromises both intelligibility and communicative participation. This study explores such complexity through a multidimensional framework grounded in Non-Linear Phonology, integrating segmental and suprasegmental measures including Whole Word Match (WWM), Word Shape Match (WSM), Stress Match (SM), and Percentage of Consonants Correct (PCC). The overall aim was to characterise the phonological development of 30 Chilean children and adolescents with DS, aged 5 to 20 years, divided into three age groups. Phonological samples were elicited using the Spanish Phonology Test (Bernhardt et al., 2016) and analysed with Phon 3.5 software (Hedlund y Rose, 2020). Analyses of variance, individual profiling via Z-scores, and Principal Component Analysis (PCA) were conducted. Results indicated significant differences across age groups for all metrics, with greater progress observed in childhood and relative stabilisation during adolescence. At the individual level, profiles were highly heterogeneous, with dissociations emerging across metrics. PCA identified a primary dimension of phonological accuracy and a secondary dimension related to stress patterns. These findings underscore the importance of applying comprehensive phonological assessments that address multiple dimensions of speech, in order to design interventions tailored to the specific phonological profiles of individuals with DS.
Keywords: Down syndrome; Phonological Development; Clinical Phonology; Nonlinear Phonology; Multidimensional Analysis